Percepciones sobre contaminacion y actitudes ambientales - Casa-Coila, Manuela-Daishy; Mamani-Jilaja, Dometila; Mamani-Quispe, Nelly-Edith; Mamani-Vilca, Paula-Soledad; Cervantes-Alagón, Sheyla; Perez-Argollo, Katia (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
The book was adapted from an investigation that was presented to the National University of the Altiplano (UNA). The objective was to determine the relationship between perceptions about the problem of environmental pollution and environmental attitudes in students of the Faculty of Educational Sciences (FCEDUC) of UNA Puno, Peru. The research method was the quantitative approach, the non-experimental type and the design was correlational. For this purpose, the population was made up of 778 students, with an intentional sample of 113 students. The data collection techniques were the evaluation technique and the Likert-type attitude test, the instruments being the test of perceptions of environmental pollution and the Likert scale of attitudes. The statistical design that was applied was the chi square (X2) for the hypothesis test. The results show that there is a significant relationship between the study variables of perceptions with attitudes about environmental problems according to the inferential statistics that was X2 = 62.534. It was concluded that the problem of environmental pollution is the task of all citizens to put into practice the care and preservation of the environment with attitudes that help not to contaminate nature.